CORRELATION OF FREE HEMOGLOBIN LEVEL AND PLASMA NITRIC OXIDE IN PACKED RED CELL DURING BLOOD BANK STORAGE PERIOD - Ricca Fitria; Zelly Dia Rofinda; Desywar Desywar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Stored red blood cells undergo morphological and biochemical changes with increased storage time, commonly refferred as the storage lesion, reduced integrity of erythrocyte membrane, causing hemolysis and increased free plasma hemoglobin level. Nitric Oxide (NO) is an endogenous vasodilator with the major role in vascular and blood flow regulation. Accumulation of free hemoglobin (fHb) during storage RBC hemolysis is thought to be correlated with elevated NO consuming causes low NO level that significantly impair endothelial function. This study aim to was to analyze the correlation of free Hb and plasma nitric oxide level during PRC storage period in the blood bank. This research was an analytic study with a cross-sectional design to 14 unit PRC those were stored in Dr. M. Djamil Padang Hospital Blood Bank. The study was conducted from May 2016 to August 2017. The assay was performed for 28 days of storage with one week intervals. Free plasma hemoglobin and NO level were analyzed by cyanmethemoglobin and colorimetry method respectively. Spearman test was used to access the correlation between free Hb level and nitric oxide plasma with p<0.05 means significant. Most donors were male (85.7%) with age range were 33(9) years. Free Hb and nitric oxide level were significantly differenced in each week storage periods (p<0.05). Two parameters was significantly had moderate negative correlation during storage periods (r=-0.56; p=0.01).